2016
DOI: 10.3171/2014.12.jns142053
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of chronic subdural hematoma drainage in nonagenarians and centenarians: a multicenter study

Abstract: o drain, or not to drain, that is the question." Chronic subdural hemorrhage (SDH) or hematoma is a predominantly neurological condition usually resulting from trauma and affecting elderly individuals. 2,3,14,19 Chronic SDH is not a benign condition and is regarded as a sentinel health event because of its high morbidity and mortality rates in older people.9,18 The treatment of choice for managing chronic SDHs is surgical drainage. 12,23 Large studies have shown that older age independently contributes to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 37 publications
4
29
1
2
Order By: Relevance
“…Even so, the results of our study indicate that patients with severe atrophy may also benefit from surgical drainage of a chronic SDH, with a better outcome in either neurological function or mental status, compared to patients with conservative treatment. These findings are consistent with other reports [16], and brain atrophy is not a contraindication for surgical drainage.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Even so, the results of our study indicate that patients with severe atrophy may also benefit from surgical drainage of a chronic SDH, with a better outcome in either neurological function or mental status, compared to patients with conservative treatment. These findings are consistent with other reports [16], and brain atrophy is not a contraindication for surgical drainage.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, patients over 80 years had significant improved in neurological status on 1-month after surgery while no statistical difference in patients with conservative treatment. Recent study suggested that surgery for CSDH is safe and positively recommended even in patients over 90 years old, with a lower rate of 6-month death [16]. The findings are consistent with our results, suggesting that patients over 80 years may be similarly able to return to their baseline function compared with younger patients, but may require longer hospital stays for further postoperative rehabilitation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations